Dysfunction of EAAT3 Aggravates LPS-Induced Post-Operative Cognitive Dysfunction - Wang, Xiao-Yan; Liu, Wen-Gang; Hou, Ai-Sheng; Song, Yu-Xiang; Ma, Yu-Long; Wu, Xiao-Dong; Cao, Jiang-Bei; Mi, Wei-Dong (Membranes (Basel), 2022)
Numerous results have revealed an association between inhibited function of excitatory amino acid transporter 3 (EAAT3) and several neurodegenerative diseases. This was also corroborated by our previous studies which showed that the EAAT3 function was intimately linked to learning and memory. With this premise, we examined the role of EAAT3 in post-operative cognitive dysfunction (POCD) and explored the potential benefit of riluzole in countering POCD in the present study. We first established a recombinant adeno-associated-viral (rAAV)-mediated shRNA to knockdown SLC1A1/EAAT3 expression in the hippocampus of adult male mice. The mice then received an intracerebroventricular microinjection of 2 μg lipopolysaccharide (LPS) to construct the POCD model. In addition, for old male mice, 4 mg/kg of riluzole was intraperitoneally injected for three consecutive days, with the last injection administered 2 h before the LPS microinjection. Cognitive function was assessed using the Morris water maze 24 h following the LPS microinjection. Animal behavioral tests, as well as pathological and biochemical assays, were performed to clarify the role of EAAT3 function in POCD and evaluate the effect of activating the EAAT3 function by riluzole. In the present study, we established a mouse model with hippocampal SLC1A1/EAAT3 knockdown and found that hippocampal SLC1A1/EAAT3 knockdown aggravated LPS-induced learning and memory deficits in adult male mice. Meanwhile, LPS significantly inhibited the expression of EAAT3 membrane protein and the phosphorylation level of GluA1 protein in the hippocampus of adult male mice. Moreover, riluzole pretreatment significantly increased the expression of hippocampal EAAT3 membrane protein and also ameliorated LPS-induced cognitive impairment in elderly male mice. Taken together, our results demonstrated that the dysfunction of EAAT3 is an important risk factor for POCD susceptibility and therefore, it may become a promising target for POCD treatment.